TESTING FEEDBACK BY USING F TEST - ISMAEEL, SHELAN SAIED (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
The present study deals with the detection of feedback between rainfall as an output series and temperature as an input series. Two methods were used. The first method is testing of cross-correlation function between prewhiten of the input and output series. The second method was used to test F between two series of input and output. The results shown that there is no feedback between input and output series presented in this study as that there, where it has founded cross-correlation between prewhiten of the input series ( ) and residual series (at) . KEYWORDS: feedback, output series, input series, residual series, Dynamic Regression